Determinants of Successful Aging in Older Adults: A Systematic Review of Psychological, Social, and Physical Factors - Yustanti, Audy Savira; Annisa, Nadiya Sahara; Indarwati, Retno; Wahyudi, Andri Setiya (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2024)
Introduction: Successful aging was defined as reaching old age with a healthy physical condition, good cognitive, and having a positive and fulfilling social life. This is supported by the existence of psychological, social, and physical factors that can influence successful aging in the older adults. The aim of this study was to describe the determinants of successful aging in older adults based on psychological, social and physical factors. Methods: The compilers of this systematic review are based on literature studies from various electronic databases, including PubMed, Scopus, CINAHL, ScienceDirect, Springer Link and ProQuest by conducting a comprehensive review using PRISMA guidelines and The Center for Review and Dissemination and the Joanna Briggs Institute Guideline as a guide in qualitaty assessment of several journals. Results: A total of 9 articles were analyzed. The determinants identifed for successful aging include including: Physical factors such as physical activity, muscle strength, and walking speed. Psychological factors such as mental health, optimism, and resilience. Social factors such as social support, social participation, and positive interpersonal relationships. Conclusions: It is concluded that there are several psychological, social, and physical factors that influence a person's success in aging well or successful aging. By paying attention to these factors, it is hoped that the elderly can maximize their potential to achieve successful aging and maintain a good quality of life while aging. Keywords: Successful Aging, Older Adults, Determinants Introduction: Successful aging was defined as reaching old age with a healthy physical condition, good cognitive, and having a positive and fulfilling social life. This is supported by the existence of psychological, social, and physical factors that can influence successful aging in the older adults. The aim of this study was to describe the determinants of successful aging in older adults based on psychological, social and physical factors. Methods: The compilers of this systematic review are based on literature studies from various electronic databases, including PubMed, Scopus, CINAHL, ScienceDirect, Springer Link and ProQuest by conducting a comprehensive review using PRISMA guidelines and The Center for Review and Dissemination and the Joanna Briggs Institute Guideline as a guide in qualitaty assessment of several journals. Results: A total of 9 articles were analyzed. The determinants identifed for successful aging include including: Physical factors such as physical activity, muscle strength, and walking speed. Psychological factors such as mental health, optimism, and resilience. Social factors such as social support, social participation, and positive interpersonal relationships. Conclusions: It is concluded that there are several psychological, social, and physical factors that influence a person's success in aging well or successful aging. By paying attention to these factors, it is hoped that the elderly can maximize their potential to achieve successful aging and maintain a good quality of life while aging.